Aligning Close Friends Feature Protection with Indonesia’s Personal Data Law: Menyesuaikan Fitur Perlindungan Teman Dekat dengan Undang-Undang Perlindungan Data Pribadi Indonesia - Al Ghifari , Mochammad Hubaib; Muis, Lidya Shery (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: The continuous digitalization of social interaction has accelerated the creation and sharing of personal data, demanding effective mechanisms to manage and protect user privacy. Specific Background: Social media platforms have introduced segmented sharing options, such as the 'Close Friend' feature, as a technical control to mitigate the risks associated with generalized data exposure. Knowledge Gap: Limited legal research has specifically analyzed the extent to which these technical features and their underlying privacy policies align with comprehensive national data protection frameworks, particularly the Indonesian Personal Data Protection Law (UU PDP No. 27/2022). Aims: This study legally analyzes the privacy policies of the 'Close Friend' feature across major social media platforms and assesses its conformity with Indonesian legal principles concerning personal data protection. Results: The feature structurally implements the Privacy by Design principle, offering users granular control over their content access. This technical protection is generally found to be in line with the principles stipulated in the Indonesian UU PDP. Novelty: This study provides a necessary comparative legal examination of a specific technical privacy feature against a new, comprehensive national data protection law, confirming the feature's legal viability. Implications: Despite technical compliance, the persistent risk of content misuse highlights the necessity for platforms, users, and regulators to collaborate in enhancing digital literacy to ensure optimal and shared responsibility for data security. Highlights Close Friend feature technically complies with the Privacy by Design legal principle. The feature's data protection mechanism is in alignment with Indonesia's Personal Data Protection Law (UU PDP). Data misuse risk remains high due to low user digital literacy and awareness. Keywords: Privacy Policy, Close Friend, Personal Data Protection, Privacy by Design, Digital Literacy.